2021
DOI: 10.3389/fphar.2021.777689
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Network Pharmacology and Lipidomics to Reveal the Inhibitory Effect of Qingfei Oral Liquid on Excessive Autophagy in RSV-Induced Lung Inflammation

Abstract: Background: Respiratory syncytial virus (RSV) can cause varying degrees of lung inflammation in children. Qingfei Oral Liquid (QF) is effective in treating childhood RSV-induced lung inflammation (RSV-LI) in clinics, but its pharmacological profiles and mechanisms remain unclear.Methods: This study combined network Pharmacology, lipidomics, pharmacodynamics, and pathway validation to evaluate the therapeutic mechanisms of QF. Using Cytoscape (v3.8.2) and enrichment analyses from the Kyoto Encyclopedia of Genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The pro-inflammatory cytokines, such as TNF-α, IL-6, and IL-1β, are vital for the onset and progression of RSV, particularly in the early phases of inflammation, and persistent elevations of these cytokines usually indicate unsatisfactory prognosis (Tabarani et al, 2013;Vázquez et al, 2019). Previous studies reported that TNF-α, IL-1β, and IL-6 levels were elevated in RSV-induced lung inflammation (Lin et al, 2021). Herein, RSV notably increased the levels of TNF-α, IL-1β, and IL-6 in lung tissue and BALF.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory cytokines, such as TNF-α, IL-6, and IL-1β, are vital for the onset and progression of RSV, particularly in the early phases of inflammation, and persistent elevations of these cytokines usually indicate unsatisfactory prognosis (Tabarani et al, 2013;Vázquez et al, 2019). Previous studies reported that TNF-α, IL-1β, and IL-6 levels were elevated in RSV-induced lung inflammation (Lin et al, 2021). Herein, RSV notably increased the levels of TNF-α, IL-1β, and IL-6 in lung tissue and BALF.…”
Section: Discussionmentioning
confidence: 99%
“…The best effect was delivered by QF at a medium dose. QF has been widely used in the treatment of pediatric respiratory diseases in China and has been approved by the Chinese National Drug administration ( Lin et al, 2021 ). Children aged about 6 years old should take one dose (crude drug 91 g) daily, which is equivalent to the medium dose of mice according to the conversion method of body surface area between mice and human.…”
Section: Discussionmentioning
confidence: 99%
“…Combining network pharmacology with molecular docking can serve as a strategy to unveil the underlying mechanisms of multiple compounds and targets of QXZKG (Wang, Li, et al, 2023). Understanding biological processes (BPs) is fundamental to network pharmacology, involving various biological information, such as protein targets and lipids (Lin et al, 2021). Lipidomics encompasses the comprehensive analysis of lipids and their biological activities, providing valuable insights into diverse physiological and pathological process (Chen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding biological processes (BPs) is fundamental to network pharmacology, involving various biological information, such as protein targets and lipids (Lin et al, 2021). Lipidomics encompasses the comprehensive analysis of lipids and their biological activities, providing valuable insights into diverse physiological and pathological process (Chen et al, 2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation